2007
DOI: 10.4049/jimmunol.178.7.4194
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-Mediated Disruption of Lymphocyte Trafficking, Hemopoiesis, and Induction of Lymphopenia, Anemia, and Thrombocytopenia in Anti-CD137-Treated Mice

Abstract: CD137-mediated signals costimulate T cells and protect them from activation-induced apoptosis; they induce curative antitumor immunity and enhance antiviral immune responses in mice. In contrast, anti-CD137 agonistic mAbs can suppress T-dependent humoral immunity and reverse the course of established autoimmune disease. These results have provided a rationale for assessing the therapeutic potential of CD137 ligands in human clinical trials. In this study, we report that a single 200-μg injection of anti-CD137 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
183
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(213 citation statements)
references
References 78 publications
21
183
6
Order By: Relevance
“…The effects in the combination arms, which included liver mixed cell infiltration and single-cell necrosis with associated increases in plasma liver enzymes, splenic lymphoid hyperplasia and extramedulary hematopoiesis, and decreases in peripheral white blood cell subsets and platelets, were driven predominantly by the anti-4-1BB antibody. These findings were observed with similar severity in the anti-4-1BB-alone treatment arms and have been described previously with another mouse-reactive anti-4-1BB (44). The human relevance of the mouse findings is apparent in a previous report listing neutropenia and transaminitis as two of the most common adverse events in a phase I trial of a 4-1BB agonist antibody in patients with cancer (45).…”
Section: Discussionsupporting
confidence: 60%
“…The effects in the combination arms, which included liver mixed cell infiltration and single-cell necrosis with associated increases in plasma liver enzymes, splenic lymphoid hyperplasia and extramedulary hematopoiesis, and decreases in peripheral white blood cell subsets and platelets, were driven predominantly by the anti-4-1BB antibody. These findings were observed with similar severity in the anti-4-1BB-alone treatment arms and have been described previously with another mouse-reactive anti-4-1BB (44). The human relevance of the mouse findings is apparent in a previous report listing neutropenia and transaminitis as two of the most common adverse events in a phase I trial of a 4-1BB agonist antibody in patients with cancer (45).…”
Section: Discussionsupporting
confidence: 60%
“…Reverse signals of CD137L enhances DC maturation and subsequent antigen-specific T-cell differentiation [36]. These together with previous studies using transgenic mice, knockout mice or mice injected with anti-CD137L Ab [19,37,38] clearly show potential in vivo effects of CD137L on innate immunity, although there are some discrepancies in the effects of CD137L. CD137L reverse signals might induce negative or positive effects on innate immunity depending on the cell CD137/CD137L are expressed and the differentiation state of that cell as suggested by Lee et al [33].…”
Section: Discussionmentioning
confidence: 94%
“…Anti-4-1BB therapy severely affects B-cell numbers and function, resulting in damping of overall humoral immunity such that autoantibody production is inhibited (13). The basis of this effect is not clear, but it is suspected that B cells are susceptible to stand-alone anti-4-1BB mAb treatment even in the absence of antigen stimulation (14). Sun and colleagues (12) showed that much of the loss of B-cell function during anti-4-1BB mAb treatment of lupus-prone mice is prevented if in vivo IFN-g is neutralized.…”
Section: Expression and Function Of 4-1bb And 4-1bblmentioning
confidence: 99%
“…Further studies uncovered the existence of an increased proportion of tumor antigen-specific CD8þ T cells in the GM-CSF/anti-4-1BB-treated mice. Chronic anti-4-1BB therapy is known to deplete CD4þ T cells (14), and this effect was found to be useful for treating autoimmune diseases (4). Choi and colleagues (47) showed a beneficial effect of CD4þ T-cell depletion on anti-4-1BB-mediated antitumor activity.…”
Section: Anti-4-1bb Combination Therapy With Other Anticancer Agentsmentioning
confidence: 99%